Pengaruh Stop Moption Graphic Berbasis Aplikasi Interaktif terhadap Kemampuan Membaca Permulaan Siswa Kelas 1 - Rahmawati, Dina Ayu; Azmy, Bahauddin (Lembaga Yasin AlSys, 2025)
This research investigates the impact of utilizing stop motion graphic learning media integrated with interactive applications on the early reading skills of first-grade students at SDN Banjarsugihan 1/116 Surabaya. Designed to foster a more engaging, enjoyable, and interactive learning environment, this media aims to enhance students' comprehension of reading materials. The study primarily examines how this learning approach aids in letter recognition, vowel and consonant differentiation, and syllable blending into meaningful words. Employing a quantitative research approach, this study adopts an experimental method with a pre-experimental design, specifically a one-group pretest-posttest design. Students' reading abilities were assessed before (pretest) and after (posttest) exposure to the stop motion graphic learning media. The findings indicate a significant improvement in early reading skills, as reflected in the increase of the average pretest score from 56.76 to 84.41, marking an average gain of 27.65 points. Hypothesis testing further confirms the effectiveness of this learning media, with a significance value (Sig. 2-tailed) of 0.000. Overall, the study concludes that stop motion graphic learning media integrated with interactive applications positively influences the early reading skills of first-grade students at SDN Banjarsugihan 1/116 Surabaya in the 2024/2025 academic year.